Discovery of cancer-preventive juices reactivating RB functions - Mitsuharu Masuda; Mano Horinaka; Shusuke Yasuda; Mie Morita; Emi Nishimoto; Hideki Ishikawa; Michihiro Mutoh; Toshiyuki Sakai (Komiyama Printing Co. Ltd, 2023)
Background: Recent advances have been achieved in the genetic diagnosis and therapies against malignancies due to a better understanding of the molecular mechanisms underlying carcinogenesis. Since active preventive methods are currently insufficient, the further development of appropriate preventive strategies is desired. Methods: We searched for drinks that reactivate the functions of tumor-suppressor retinoblastoma gene (RB) products and exert anti-inflammatory and antioxidant effects. We also examined whether lactic acid bacteria increased the production of the cancer-specific anti-tumor cytokine, tumor necrosis factor-related apoptosis-inducing ligand (TRAIL), in human, and examined whether the RB-reactivating drinks with lactic acid bacteria decreased azoxymethane-induced rat colon aberrant crypt foci (ACF) and aberrant crypts (ACs) in vivo. Results: Kakadu plum juice and pomegranate juice reactivated RB functions, which inhibited the growth of human colon cancer LIM1215 cells by G1 phase arrest. These juices also exerted anti-inflammatory and antioxidant effects. Lactiplantibacillus (L.) pentosus S-PT84 was administered to human volunteers and increased the production of TRAIL. In an in vivo study, Kakadu plum juice with or without pomegranate juice and S-PT84 significantly decreased azoxymethane-induced rat colon ACF and ACs. Conclusions: RB is one of the most important molecules suppressing carcinogenesis, and to the best of our knowledge, this is the first study to demonstrate that natural drinks reactivated the functions of RB. As expected, Kakadu plum juice and pomegranate juice suppressed the growth of LIM1215 cells by reactivating the functions of RB, and Kakadu plum juice with or without pomegranate juice and S-PT84 inhibited rat colon ACF and ACs. Therefore, this mixed juice has potential as a novel candidate for cancer prevention.